Laminin-bound integrin α6β4 promotes non-small cell lung cancer progression via the activation of YAP/TAZ signaling pathway - Zhao, Xiaopeng; Liu, Chuang; He, Xu; Wang, Miao; Zhang, Haoran; Cheng, Jingge; Wang, Hongyan (Frontiers in Oncology, 2022)
Laminin is an extracellular matrix multidomain trimeric glycoprotein, that has a potential role in tumor progression. Here, we studied the effects of non-small cell lung cancer (NSCLC) cells interaction on laminin and explored the underlying mechanism of laminin associated NSCLC progression. Culture of A549 and NCI-1299 cells on 2D collagen gels (containing laminin) significantly promoted the proliferative and tumorigenic characteristics, as well as cell invasion of tumor cells in vitro. Consistently, comparing the clinical NSCLC tumor tissues, a poor overall survival was observed in patients with high laminin expression. Mechanistically, the expression of integrin α6β4 was required for the pro-tumor effects of laminin. Meanwhile, we showed that the downstream signaling of integrin α6β4, involved the focal adhesion kinase (FAK)/ Yes-Associated Protein (YAP)/TAZ signaling pathway. The activation of FAK/YAP/TAZ signaling pathway induced by laminin was validated in tumor tissues from NSCLC patients. Suppression of integrin α6β4/FAK/YAP/TAZ signaling pathway efficiently suppressed the laminin-induced tumor growth, and strengthened the anticancer effects of chemotherapy, describing a novel target for NSCLC treatment.